DETERMINAN PAJAK DAERAH, RETRIBUSI DAERAH DAN PENDAPATAN PERKAPITA TERHADAP PENDAPATAN ASLI DAERAH - Afifah, Maranti; Hambani, Susy; Anwar, Saepul (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2024)
The aim of this research is to explore the impact of regional taxes, regional levies and per capita income on local original income. The analytical method used is panel data regression. The research sample consists of Regency and City Government Financial Reports in the West Java Province region for 2018 - 2022, using a saturated sampling technique where all members of the population are used as samples. This research found that regional taxes partially have an influence on local original income, while regional levies and per capita income do not show a significant influence on local original income. Meanwhile, regional taxes, regional levies and per capita income simultaneously influence regional original income.